2018
DOI: 10.1002/cam4.1865
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for brain metastases in patients with non–small‐cell lung cancer

Abstract: Brain metastases (BM) are severe incidents in patients with non–small‐cell lung cancer (NSCLC). The controversial value of prophylactic cranial irradiation (PCI) in NSCLC in terms of survival benefit prompted us to explore the possible risk factors for BM in NSCLC and identify the potential population most likely to benefit from PCI. Risk factors for brain metastases in NSCLC are reviewed in this article. Identifying patients with a higher risk of BM could possibly increase the benefit of PCI while reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 89 publications
6
31
1
2
Order By: Relevance
“…Furthermore, our results confirmed that the predictive value of gender and KPS score for metachronous BM may remain controversial [35]. Previous studies reported that elevated CEA [20,21,35], NSE [29], and CA125 [29] were independent risk factors of BM. However, there is no correlation between tumor markers levels before treatment (including CEA, NSE, and CA125) and the metachronous BM in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, our results confirmed that the predictive value of gender and KPS score for metachronous BM may remain controversial [35]. Previous studies reported that elevated CEA [20,21,35], NSE [29], and CA125 [29] were independent risk factors of BM. However, there is no correlation between tumor markers levels before treatment (including CEA, NSE, and CA125) and the metachronous BM in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, our results con rmed that the predictive value of gender and KPS score for metachronous BM may remain controversial [35]. Previous studies reported that elevated CEA [20,21,35], NSE [29], and CA125 [29] were independent risk factors of BM. However, there is no correlation between tumor markers levels before treatment (including CEA, NSE, and CA125) and the metachronous BM in our study.…”
Section: Discussionsupporting
confidence: 71%
“…[27][28][29][30] However, our results regarding age distribution and metastatic spread are in line with others since we also found that brain metastases appeared more frequently in the younger population and bone metastases among elderly patients. [30][31][32] A possible explanation might be that brain metastases are associated with the angiogenic microenvironment, and the cerebrovascular microenvironment factors of young patients may be better than those of older patients, while in the case of bone metastases the more favorable bone marrow microenvironment for metastatic spread and the higher incidence of osteoporosis in elderly patients might contribute to the higher incidence of bone metastases. 31,33,34 Next, we focused on the longitudinal changes of the measured CBC parameters during cancer progression and metastatic spread, and found significant changes with regard to all parameters in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] A possible explanation might be that brain metastases are associated with the angiogenic microenvironment, and the cerebrovascular microenvironment factors of young patients may be better than those of older patients, while in the case of bone metastases the more favorable bone marrow microenvironment for metastatic spread and the higher incidence of osteoporosis in elderly patients might contribute to the higher incidence of bone metastases. 31,33,34 Next, we focused on the longitudinal changes of the measured CBC parameters during cancer progression and metastatic spread, and found significant changes with regard to all parameters in the experimental group. According to the longitudinal analysis, we found significantly decreasing ALC in all patient subgroups irrespective of histopathological and metastatic types.…”
Section: Discussionmentioning
confidence: 99%